Finding What Is Lost: The Intangible Archive of València’s Falles Festival - Horner, Rachel (MUSICultures, 2025)
What remains in the archive when its material objects are constructed with the aim of destruction? Scholarly approaches to the “self-destructive archive” have emphasized ways to manipulate the archive to circumvent its inevitable drive toward loss. The Falles Festival of València, Spain, offers a different perspective: through the burning of the monumental artworks that give the festival its name, an “intangible archive” of behaviours, feelings, and beliefs comes into being, one that structures and is structured by social life during and beyond the festival. This archive affords ethnomusicologists a means to reconceptualize the material nature of ephemeral phenomena like sound.